Silver-Catalyzed Three-Component Approach to Quinolines Starting from Anilines, Aldehydes, and Alcohols - Zhang, Xu; Liu, Wenmin; Sun, Ruixue; Xu, Xuefeng; Wang, Zhiqiang; Yan, Yanlei (Synlett, 2016)
A silver-catalyzed sequential formation of two C–C bonds for the construction of a series of polysubstituted quinolines from anilines, aldehydes, and alcohols under mild conditions has been developed. The transformation is effective for a broad range of substrates, including aliphatic alcohols, arylalkanols, cycloalkanols, and ethylene glycol, thereby permitting the expansion of the constituent architectures of the heterocyclic framework.
Keywords: silver; catalysis; amines; aldehydes; alcohols; quinolines